Pediatric to adult healthcare transitioning for adolescents living with HIV in Nigeria: A national survey. - Okikiolu A Badejo; William N A Menson; Nadia A Sam-Agudu; Jennifer Pharr; Salome Erekaha; Tamara Bruno; Gift Nwanne; Olabanjo Ogunsola; Jude Ilozumba; Olusegun Busari; Echezona E Ezeanolue (PLoS ONE)
Introduction The period of transition from pediatric to adult care has been associated with poor health outcomes among 10-19 year old adolescents living with HIV (ALHIV). This has prompted a focus on the quality of transition services, especially in high ALHIV-burden countries. Due to lack of guidelines, there are no healthcare transition standards for Nigeria's estimated 240,000 ALHIV. We conducted a nationwide survey to characterize routine transition procedures for Nigerian ALHIV. Materials and methods This cross-sectional survey was conducted at public healthcare facilities supported by five local HIV service implementing partners. Comprehensive HIV treatment facilities with ≥1 year of HIV service provision and ≥20 ALHIVs enrolled were selected. A structured questionnaire assessed availability of treatment, care and transition services for ALHIV. Transition was defined as a preparatory process catering to the medical, psychosocial, and educational needs of adolescents moving from pediatric to adult care. Comprehensive transition services were defined by 6 core elements: policy, tracking and monitoring, readiness evaluation, planning, transfer of care, and follow-up. Results All 152 eligible facilities were surveyed and comprised 106 (69.7%) secondary and 46 (30.3%) tertiary centers at which 17,662 ALHIV were enrolled. The majority (73, 48.3%) of the 151 facilities responding to the "clinic type" question were family-centered and saw all clients together regardless of age. Only 42 (27.8%) facilities had an adolescent-specific HIV clinic; 53 (35.1%) had separate pediatric/adolescent and adult HIV clinics, of which 39 (73.6%) reported having a transfer/transition policy. Only 6 (15.4%) of these 39 facilities reported having a written protocol. There was a bimodal peak at 15 and 18 years for age of ALHIV transfer to adult care. No surveyed facility met the study definition for comprehensive transition services. Conclusions Facilities surveyed were more likely to have non-specialized HIV treatment services and had loosely-defined, abrupt transfer versus transition practices, which lacked the core transition elements. Evidence-based standards of transitional care tailored to non-specialized HIV treatment programs need to be established to optimize transition outcomes among ALHIV in Nigeria and in similar settings.